2010
DOI: 10.1016/j.apenergy.2009.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate electricity demand in South Africa: Conditional forecasts to 2030

Abstract: In 2008, South Africa experienced a severe electricity crisis. Domestic and industrial electricity users had to suffer from black outs all over the country. It is argued that partially the reason was the lack of research on energy, locally. However, Eskom argues that the lack of capacity can only be solved by building new power plants.The objective of this study is to fill part of the gap of the energy research in the country. By using the Engle Granger methodology for co-integration and Error Correction Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 37 publications
4
76
0
Order By: Relevance
“…The first attempt to estimate the influence of electricity prices to its consumption was made by Pouris (1987). Since then different econometric approaches have been used to assess the impact of price (Inglesi, 2010;Ziramba, 2008, Amusa et al, 2009Inglesi-Lotz and Pouris, 2010;Inglesi-Lotz, 2011).. Ziramba (2008) examined the residential electricity demand and found that for the period 1978 to 2005, price of electricity was insignificant in the long-run. Amusa et al (2009) also found that electricity prices …”
Section: Determinants Of Energy and Electricity Demand In South Africamentioning
confidence: 99%
See 2 more Smart Citations
“…The first attempt to estimate the influence of electricity prices to its consumption was made by Pouris (1987). Since then different econometric approaches have been used to assess the impact of price (Inglesi, 2010;Ziramba, 2008, Amusa et al, 2009Inglesi-Lotz and Pouris, 2010;Inglesi-Lotz, 2011).. Ziramba (2008) examined the residential electricity demand and found that for the period 1978 to 2005, price of electricity was insignificant in the long-run. Amusa et al (2009) also found that electricity prices …”
Section: Determinants Of Energy and Electricity Demand In South Africamentioning
confidence: 99%
“…In the international literature in accordance to basic economic theory, the demand of a good or a service is usually dependent on factors such as its own price, the income of the consumers, the price of substitute goods and other exogenous variables related to the nature of the good (Inglesi, 2010). The majority of international studies include as main explanatory variables the income of the consumers (or economic growth) and the price of energy (electricity) (for example, Atakhanova and Howie (2007) Nasr et al (2000); ).…”
Section: Determinants Of Energy and Electricity Demand In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…(8) includes standard variables, used in international and local literature (Inglesi, 2010;Nakajima and Hamori, 2010;Dilaver and Hunt, 2010) such as prices of electricity and output of the economy, to explain the electricity consumption.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Although the effects of the electricity prices to the electricity consumption in South Africa are well documented (Ziramba, 2008;Inglesi, 2010;Inglesi-Lotz, 2011;Inglesi-Lotz and Blignaut, 2011;Inglesi-Lotz, 2014;Inglesi-Lotz and Pouris, forthcoming), the nature of the evolution of electricity prices in South Africa was never examined in the literature.…”
Section: Introductionmentioning
confidence: 99%